EFFECT OF PERCEIVED ORGANIZATIONAL JUSTICE TO COMMITMENT AND TURNOVER INTENTION AMONG IBA LECTURERS FACULTY OF ECONOMICS AND BUSINESS UNIVERSITY OF SAM RATULANGI MANADO - Liando, Anastasya C. (Universitas Sam Ratulangi, 2014)
This study attempts to investigate the effect of organizational justice, commitment and turnover intention among lecturers in International Business Administration Study Program in Faculty of Economics and Business Sam Ratulangi University. A total of 9 respondents throughout the Lecturers of IBA Study Program of Faculty of Economics and business (FEB) Sam Ratulangi University (UNSRAT) participated in this study. The method used in this research is the qualitative research methodology through in-depth interview which will provide a descriptive insight about the effect of perceived organizational justice to commitment and turnover intention among lecturers. The data was gathered from interviews and observation which the samples are the lecturers of IBA study program. The result showed that there is a significant effect of distributive justice to both permanent lecturers or public servant and temporary lecturers’ commitment and moderate effect of procedural justice to both permanent lecturers and temporary lecturers’ commitment. Both distributive and procedural justice have no significant effect to permanent lecturers or public servants and have significant effect to temporary lecturers. These findings have important implications for leader or managers in formulating appropriate policies and procedures to improve employees’ commitment to their organizations and to reduce their turnover intentions. Keywords: organizational justice, commitment, turnover intention